A potential-responsive affinity-controlling 2-2′-dithiodibenzoic acid/polyaniline hybrid film with high ion exchange capability and selectivity to cadmium ions. (1st October 2019) - Wang, Zhongde; Du, Juan; Yan, Wenjun; Zhang, Wei; Niu, Junjian; Wu, Ailian; Hao, Xiaogang; Guan, Guoqing
Abstract: A potential-responsive 2-2′-dithiodibenzoic acid (DTSA)/Polyaniline (PANI) hybrid film with high ion-exchange capability and selectivity to cadmium ions was successfully fabricated on electrode by a one-step cyclic voltammetry (CV) method. S–S bonds in the DTSA serve as a gate that can be controllably opened and closed to let cadmium ions get in and out of the hybrid film when changing its redox state, and the PANI mainly enhanced the conductivity of the hybrid film. The working mechanism of the film is proposed and identified via the electrochemical quartz crystal microbalance (EQCM) technique, X-ray photoelectron spectroscopy (XPS), Raman and density functional theory (DFT) computations. As a result, the obtained hybrid film exhibited high selectivity towards cadmium ions even in the presences of other cations. More interestingly, over 240% of its initial capacity was retained after 25 consecutive cycles and maintained in the following cycles. Furthermore, the regeneration rate of the hybrid film retains 99% of its initial value even after 30 cycles. It is expected that such a potential-responsive film can be applied for the removal and recovery of cadmium ions from wastewater in various industrial processes. Graphical abstract: Image 1 Highlights: S–S bonds can be controllably to let Cd 2+ get in and out of the hybrid film. The obtained hybrid film exhibited a high selectivity towards Cd 2+ ions. The regeneration rate of film retains 99% of its initial value after 30 cycles. It is function as the ion-probe which accelerates the uptaking rate of cadmium.